La importancia de las políticas de desclasificación en el desarrollo de los estudios de inteligencia - Díaz Matey, Gustavo (UNISCI Discussion Papers, 2011)
The declassification of official archives is one of the most urgent necessities in the advancement of intelligence studies world-wide as it represents a unique form of accessing primary sources that serve not only as an indicator of the state’s commitment to this discipline, but also as a key element in developing clear and shared theoretic foundations. In fact, increased declassification results in a greater development of intelligence studies, resulting in greater knowledge of the intelligence culture in the country that declassifies the information.This article will develop the above idea by comparing the declassification policies in Great Britain, the United States and Russia and its former republics with those of Spain.